Medication Adherence and the Role of Pictograms in Medication Counselling of Chronic Patients: a Review - Piotr Merks; Piotr Merks; Jameason Cameron; Krzysztof Bilmin; Damian Świeczkowski; Tomira Chmielewska-Ignatowicz; Tomasz Harężlak; Katarzyna Białoszewska; Katarina Fehir Sola; Miłosz J Jaguszewski; Regis Vaillancourt (Frontiers Media S.A., 2021)
Pharmaceutical care requires a patient-centered approach, focusing on the ability of patients to understand drug-related information and follow the instructions delivered by pharmacists as well as other health-care providers included in the circle of care. With the goal of ensuring the prescribed use of medications, called medication adherence, health-care providers have to consider many risk factors such as geography (culture), social economic status, age, and low literacy that may predispose patients to non-adherence, and considerations have to be made for chronic patients living with life-long disease states. The aim of this review is to provide a balanced and comprehensive review outlining a number of different medication counselling and education approaches that have been used to try to improve medication adherence and health outcomes with the use of clear and concise graphic illustrations-called pictograms. By highlighting the current landscape of the general use and efficacy of pharmaceutical pictograms to aid in the knowledge and recall of drug-related information, as well as outlining specific medication adherence outcomes with pharmaceutical pictograms in chronic patients, the current review describes the need for health-care providers to move beyond the traditional didactic methods of oral and verbal communication with patients regarding medication-taking behavior.